Guided use of writing prompts to improve academic writing in college students (2011)
The paper presents empirical data supporting the hypothesis that the systematic and guided use of academic writing prompts is a successful instructional strategy to improve the academic writing in Spanish of college students, mainly during their first semesters. A combined methodology, with pre- and post-tests, was used in this research project conducted from July 2009 to June 2010. The participants were freshmen students of different disciplines of the Human Sciences in a private university in Bogota, Colombia. The aim of this research project was twofold. First, it sought to identify the difficulties students faced in the writing process of academic texts when they are related to real communicative contexts. Second, it involved the design and application of the guided and systematic use of writing prompts for academic writing in a sequence called "The Cognitive Pedagogical Model of Writing for Higher Education". The results show empirical evidence supporting the use of writing prompts designed with specific academic purposes to improve the academic writing level of college students in their first stages of study. However, further research is needed to consolidate the results presented here.